Analisis Kesenjangan Pelayanan Pada Pasien Poliklinik Rawat Jalan Menggunakan Customer Window - Linta Meyla Putri; Stefanus Supriyanto; Linta Meyla Putri (Universitas Airlangga, 2016)
Patient complaints toward service at Undaan Eyes Hospital in 2015 amounted to 9 complaints, and has not yet reached target set by the hospital which was equal to 0 complaints. Therefore, the purpose of this research is to analyze gaps in expected service and perceived service of responsiveness, reliability and emphatyat UndaanEyes Hospital. This research was an analytic observational survey and to be analyzed by customer window. Sample were in equal to 98 people and collected by systematic random sampling. The result showed from the analysis of the customer windowwas that some aspects in service are in quadrant A or Attention, which patient expected service higher than perceived service. Some aspects that were in Attention quadrant, are: waiting time > 30 minutes, speed of service delivery was slow and lack information. It can be concluded that some of the things that are in quadrant A or Attention is a strategic issue that must consider and resolve byUndaan Eyes Hospital to meet the expectations of patients. Keywords: customer window, gap analysis,service